Mycobacterium tuberculosis Co-operonic PE32/PPE65 Proteins Alter Host Immune Responses by Hampering Th1 Response - Khubaib, Mohd; Sheikh, Javaid A.; Pandey, Saurabh; Srikanth, Battu; Bhuwan, Manish; Khan, Nooruddin; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Microbiology, 2016)
PE/PPE genes, present in cluster with ESAT-6 like genes, are suspected to have a role in antigenic variation and virulence of Mycobacterium tuberculosis. Their roles in immune evasion and immune modulation of host are also well documented. We present evidence that PE32/PPE65 present within the RD8 region are co-operonic, co-transcribed and co-translated, and play role in modulating host immune responses. Experiments with macrophage cell lines revealed that this protein complex suppresses pro-inflammatory cytokines such as TNF-α and IL-6 whereas also inducing high expression of anti-inflammatory IL-10. Immunization of mice with these recombinant proteins dampens an effective Th1 response as evident from reduced frequency of IFN-g and IL-2 producing CD4+ and CD8+ T cells. IgG sub-typing from serum of immunized mice revealed high levels of IgG1 when compared with IgG2a and IgG2b. Further IgG1/IgG2a ratio clearly demonstrated that the protein complex manipulates the host immune response favourable to the pathogen. Our results demonstrate that the co-transcribed and co-translated PE32 and PPE65 antigens are involved specifically in modulating anti-mycobacterial host immune response by hampering Th1 response.